Home » Partial Fractions

Tag: Partial Fractions

Find the slope and area under the graph for a given function

Let

    \[ f(x) = \sqrt{\frac{4x+2}{x(x+1)(x+2)}} \qquad \text{for} \quad x> 0. \]

  1. Determine the slope of the graph of f at the point with x-coordinate 1.
  2. Find the volume of the solid of revolution formed by rotating the region between the graph of f(x) and the interval [1,4] about the x-axis.

  1. To take this derivative, using logarithmic differentiation will be easier,

        \begin{align*}  \log (f(x)) &= \log \left( \sqrt{ \frac{4x+2}{x(x+1)(x+2)}} \right) \\[9pt]  &= \frac{1}{2} \left( \log (4x+2) - \log (x(x+1)(x+2)) \right) \\[9pt]  &= \frac{1}{2} \left( \log (4x+2) - \log x - \log (x+1) - \log (x+2) \right). \end{align*}

    Then differentiating both sides we have,

        \begin{align*}  &&\frac{f'(x)}{f(x)} &= \frac{1}{2} \left( \frac{4}{4x+2} - \frac{1}{x} - \frac{1}{x+1} - \frac{1}{x+2} \right) \\[9pt] \implies && f'(x) &= \frac{1}{2} \sqrt{\frac{4x+2}{x(x+1)(x+2)}} \left( \frac{2}{2x+1} - \frac{1}{x} - \frac{1}{x+1} - \frac{1}{x+2} \right). \end{align*}

    So, to find the slope at the point with x = 1 we evaluate,

        \[ f'(1) = \frac{1}{2} \left( \frac{2}{3} - 1 - \frac{1}{2} - \frac{1}{3} \right) = -\frac{7}{12}. \]

  2. First, the integral to compute the volume of the solid of revolution is,

        \begin{align*}  V &= \pi \int_1^4 (f(x))^2 \, dx \\[9pt]   &= \int_1^4 \frac{\pi(4x+2)}{x(x+1)(x+2)} \, dx. \end{align*}

    To evaluate this we use the partial fraction decomposition,

        \[ \frac{2x+1}{x(x+1)(x+2)} = \frac{A}{x} + \frac{B}{x+1} + \frac{C}{x+2}. \]

    This gives us the equation

        \[ A(x+1)(x+2) + B(x)(x+2) + C(x)(x+1) = 2x+1. \]

    Evaluating at x = 0, x = -1, and x = -2 we obtain

        \[ A = \frac{1}{2}, \quad B = 1, \quad C = -\frac{3}{2}. \]

    Therefore, we have

        \begin{align*}  V &= 2 \pi \int_1^4 \left( \frac{1}{2x} + \frac{1}{x+1} - \frac{3}{2(x+2)} \right) \, dx \\[9pt]  &= 2 \pi \left( \frac{1}{2} \int_1^4 \frac{1}{x} \,dx + \int_1^4 \frac{1}{x+1} \, dx - \frac{3}{2} \int_1^4 \frac{1}{x+2} \, dx \right) \\[9pt]  &= \pi \log x \Bigr \rvert_1^4 + 2 \pi \log |x+1| \Bigr \rvert_1^4  - 3 \pi \log |x+2| \Bigr \rvert_1^4 \\[9pt]  &= \pi \log 4 + 2 \pi (\log 5 - \log 2) - 3 \pi (\log 6 - \log 3) \\[9pt]  &= 2 \pi \log 2 + 2 \pi \log 5 - 2 \pi \log 2 - 3 \pi \log (2 \cdot 3) + 3 \pi \log 3 \\[9pt]  &= 2 \pi \log 5 - 3 \pi \log 2 - 3 \pi \log 3  + 3 \pi \log 3 \\[9pt]  &= 2 \pi \log 5 - 3 \pi \log 2 \\[9pt]  & = \pi (\log 25 - \log 8) \\[9pt]  & = \pi \log \frac{25}{8}. \end{align*}

Evaluate the integral of (3 – x2)1/2 / x

Compute the following integral.

    \[ \int \frac{\sqrt{3-x^2}}{x} \, dx. \]


First, we multiply the numerator and denominator by \sqrt{3-x^2} and do some rearranging to get a friendlier integral,

    \begin{align*}  \int \frac{\sqrt{3-x^2}}{x} \, dx &= \int \frac{3-x^2}{x \sqrt{3-x^2}} \, dx \\[9pt]  &= - \int \frac{x}{\sqrt{3-x^2}} \, dx + 3 \int \frac{1}{x \sqrt{3-x^2}} \, dx. \end{align*}

For the integral on the left we make the substitution u = 3-x^2, du = -2x \, dx and obtain

    \[ -\int \frac{x}{\sqrt{3-x^2}} \, dx = \frac{1}{2} \int \frac{du}{\sqrt{u}} = \sqrt{u} = \sqrt{3-x^2}. \]

Then, for the integral on the right we make the substitution u = \sqrt{3-x^2}, du = \frac{-x}{\sqrt{3-x^2}} \, dx. This gives us

    \[ x = \sqrt{3-u^2}, \qquad dx = -\frac{\sqrt{3-x^2}}{x}. \]

Therefore for the integral on the right we have

    \begin{align*}  3 \int \frac{1}{x\sqrt{3-x^2}} \, dx &= 3 \int \frac{1}{3-u^2} \, du \\[9pt]  &= -3 \int \frac{1}{(\sqrt{3} + u)(\sqrt{3} - u)} \, du. \end{align*}

Now, we have to use partial fractions on the integrand,

    \[ \frac{1}{(\sqrt{3} + u)(\sqrt{3} - u)} = \frac{A}{\sqrt{3} + u} + \frac{B}{\sqrt{3} - u}. \]

This gives us the equation

    \[ A(\sqrt{3} - u) + B(\sqrt{3} + u) = 1 \quad \implies \quad A = B = \frac{1}{2\sqrt{3}}. \]

So,

    \begin{align*}  -3 \int \frac{1}{(\sqrt{3} + u)(\sqrt{3} - u)} \, du &= -3 \int \left(\frac{1}{2 \sqrt{3} (\sqrt{3} + u)} - \frac{1}{2 \sqrt{3} (\sqrt{3} - u)} \right) \, du \\[9pt]  &= -\frac{\sqrt{3}}{2} \left( \frac{1}{\sqrt{3} + u} \, du + \int \frac{1}{\sqrt{3} - u} \, du \right) \\[9pt]  &= -\frac{\sqrt{3}}{2} \left( \log | \sqrt{3} + u | - \log | \sqrt{3} - u | \right). \end{align*}

Putting these integrals back into our original expression we have

    \begin{align*}  \int \frac{\sqrt{3-x^2}}{x} \, dx &= -\int \frac{x}{\sqrt{3-x^2}} \, dx + 3 \int \frac{1}{x \sqrt{3-x^2}} \, dx \\[10pt]  &= \sqrt{3-x^2} - \frac{\sqrt{3}}{2} \left( \log | \sqrt{3} + u| - \log | \sqrt{3} - u| \right) \\[10pt]  &= \sqrt{3-x^2} - \frac{\sqrt{3}}{2} \log \left| \frac{\sqrt{3} + \sqrt{3-x^2}}{\sqrt{3} - \sqrt{3-x^2}} \right| + C \\[10pt]  &= \sqrt{3-x^2} - \frac{\sqrt{3}}{2} \log \left| \frac{(\sqrt{3} + \sqrt{3-x^2})^2}{x^2} \right| + C \\[10pt]  &= \sqrt{3-x^2} - \sqrt{3} \log \left( \frac{\sqrt{3} + \sqrt{3-x^2}}{x} \right) + C. \end{align*}

Evaluate the integral of 1 / (x4 + 1)

Compute the following integral.

    \[ \frac{dx}{x^4+1}. \]


First, we need to rewrite the denominator as a product of linear and quadratic terms so that we can use partial fraction decomposition. To that end, we have

    \[ x^4 + 1 = (x^2 - \sqrt{2} \, x + 1)(x^2 + \sqrt{2} \, x + 1). \]

Then we write,

    \[ \frac{1}{x^4+1} = \frac{Ax+B}{x^2-\sqrt{2} \, x +1} + \frac{Cx+D}{x^2 + \sqrt{2}\, x + 1}. \]

This gives us the equation

    \[ (Ax+B)(x^2+\sqrt{2} \, x + 1) + (Cx+D)(x^2 - \sqrt{2} \, x + 1) = 1. \]

Here we multiply everything out and equate like powers of x. Multiplying out, and grouping like powers of x give us,

    \[ (A+C) x^3 + (A\sqrt{2}+B-C\sqrt{2}+D) x^2 + (A+B\sqrt{2}+C-D\sqrt{2}) x + (B+D) = 1. \]

From this we have the system of equations

    \begin{align*}  A+C &= 0 \\ A\sqrt{2} + B - C \sqrt{2} + D &= 0 \\ A+B \sqrt{2} + C - D \sqrt{2} &= 0 \\ B+D &= 1. \end{align*}

Solving this system (sorry, I’m omitting the details of solving the system… there’s nothing tricky in it, but it’s tedious to TeX up into the blog) we obtain

    \[ A = -\frac{1}{2\sqrt{2}}, \quad B = \frac{1}{2}, \quad C = \frac{1}{2\sqrt{2}}, \quad D = \frac{1}{2}. \]

Therefore, we have

    \begin{align*}  \int \frac{dx}{x^4+1} &= \int \left( \frac{Ax+B}{x^2-\sqrt{2} \, x +1} + \frac{Cx+D}{x^2+\sqrt{2}\,x+1} \right) \, dx \\[10pt]  &= \frac{1}{4\sqrt{2}} \left(- \int \frac{2x-\sqrt{2} \, dx}{x^2-\sqrt{2} \, x +1} + \int \frac{\sqrt{2} \, dx}{x^2-\sqrt{2}\, x+1} \right. \\ &\qquad \qquad \left.+ \int \frac{2x+\sqrt{2} \, dx}{x^2+\sqrt{2} \, x + 1} + \int \frac{\sqrt{2} \, dx}{x^2+\sqrt{2} \, x + 1}\right)\\[10pt]  &= \frac{1}{4\sqrt{2}} \left( \log \left| x^2 + \sqrt{2} \, x + 1\right| - \log \left| x^2 - \sqrt{2} \, x + 1 \right| \right) \\  & \qquad \qquad  + \frac{1}{4} \int \frac{dx}{x^2+\sqrt{2} \, x + 1} + \frac{1}{4} \int \frac{dx}{x^2 -\sqrt{2} \, x + 1} \\[10pt]  &= \frac{1}{4\sqrt{2}} \log \left| \frac{x^2+\sqrt{2} \, x+1}{x^2-\sqrt{2} \, x +1} \right| + \frac{1}{4} \int \frac{dx}{\left(x+\frac{\sqrt{2}}{2}\right)^2 + \frac{1}{2}} + \frac{1}{4} \int \frac{dx}{\left(x-\frac{\sqrt{2}}{2}\right)^2+\frac{1}{2}} \\[10pt]  &= \frac{1}{4\sqrt{2}} \log \left| \frac{x^2+\sqrt{2} \, x+1}{x^2-\sqrt{2} \, x +1} \right| + \frac{1}{2} \int \frac{dx}{(\sqrt{2}\, x+1)^2 +1} + \frac{1}{2} \int \frac{dx}{(\sqrt{2}\, x -1)^2 +1} \\[10pt]  &= \frac{1}{4\sqrt{2}} \log \left| \frac{x^2+\sqrt{2} \, x+1}{x^2-\sqrt{2} \, x +1} \right| + \frac{1}{2\sqrt{2}} \int \frac{\sqrt{2} \, dx}{(\sqrt{2} \, x + 1)^2 + 1} + \frac{1}{2 \sqrt{2}} \int \frac{\sqrt{2} \, dx}{(\sqrt{2} \, x - 1)^2 + 1} \\[10pt]  &= \frac{1}{4\sqrt{2}} \log \left| \frac{x^2+\sqrt{2} \, x+1}{x^2-\sqrt{2} \, x +1} \right| + \frac{1}{2 \sqrt{2}} \left( \arctan (\sqrt{2} \, x + 1) + \arctan (\sqrt{2} \, x - 1) \right) + C. \end{align*}

Now, we want to simplify the \arctan expressions (to get our answer to match the answer Apostol provided in the back of the book). So, we use the identity

    \[ \arctan (x) + \arctan (y) = \arctan \left( \frac{x + y}{1 - xy} \right). \]

Therefore,

    \begin{align*} \arctan (\sqrt{2} \, x + 1) + \arctan (\sqrt{2} \, x - 1) &= \arctan \left( \frac{\sqrt{2} \, x + 1 + \sqrt{2} \, x - 1}{1 - (\sqrt{2}\ , x +1)(\sqrt{2} \, x - 1)} \right)\\  &= \arctan \left( \frac{2\sqrt{2} \, x}{2-2x^2} \right) \\  &= \arctan \left( \frac{\sqrt{2} \, x}{1-x^2} \right). \end{align*}

Finally, putting this back into the formula we obtained above, we have

    \[ \int \frac{dx}{x^4 + 1} = \frac{1}{4\sqrt{2}} \log \left| \frac{x^2+\sqrt{2} \, x+1}{x^2-\sqrt{2} \, x +1} \right| + \frac{1}{2\sqrt{2}} \arctan \left( \frac{\sqrt{2} \, x}{1-x^2} \right) + C. \]

Evaluate the integral of 1 / (x4 – 1)

Compute the following integral.

    \[ \int \frac{dx}{x^4-1}. \]


First, we factor the denominator

    \[ x^4 - 1= (x^2 - 1)(x^2+1) = (x-1)(x+1)(x^2+1). \]

To apply partial fraction decomposition we then write,

    \[ \frac{1}{x^4-1} = \frac{A}{x-1} + \frac{B}{x+1} + \frac{Cx+D}{x^2+1}. \]

This gives us the equation

    \[ A(x+1)(x^2+1) + B(x-1)(x^2+1) + (Cx+D)(x-1)(x+1) = 1. \]

First, we evaluate the equation at x = 1 and x = -1 to obtain

    \begin{align*}  4A &= 1 & \implies \qquad A &= \frac{1}{4} \\  -4B &= 1 & \implies \qquad B &= -\frac{1}{4}. \end{align*}

Then, using these values of A and B we evaluate at x = 0 to obtain

    \[ \frac{1}{4} + \frac{1}{4} - D = 1 \qquad \implies \qquad D = -\frac{1}{2}. \]

Finally, equating like powers of x in the equation we must have C = 0. Therefore,

    \begin{align*}  \int \frac{1}{x^4-1} \, dx &= \int \left( \frac{A}{x-1} + \frac{B}{x+1} + \frac{Cx+D}{x^2+1} \right) \, dx \\[9pt]  &= \frac{1}{4} \int \frac{1}{x-1} \, dx - \frac{1}{4} \int \frac{1}{x+1} \, dx - \frac{1}{2} \int \frac{1}{x^2+1} \, dx \\[9pt]  &= \frac{1}{4} \log |x-1| - \frac{1}{4} \log |x+1| - \frac{1}{2} \arctan x + C\\[9pt]  &= \frac{1}{4} \log \left| \frac{x-1}{x+1} \right| - \frac{1}{2} \arctan x + C. \end{align*}

Evaluate the integral of (x4 + 1) / (x (x2 + 1)2)

Compute the following integral.

    \[ \int \frac{x^4 + 1}{x(x^2+1)^2} \, dx.\]


The denominator is already factored, so we write

    \[ \frac{x^4+1}{x(x^2+1)^2} = \frac{A}{x} + \frac{Bx+C}{x^2+1} + \frac{Dx+E}{(x^2+1)^2}. \]

This gives us the equation

    \[ A(x^2+1)^2 + (Bx+C)(x)(x^2+1) + (Dx+E)x = x^4 + 1. \]

First, we can evaluate at x = 0 to obtain

    \[ A = 1. \]

Then, we multiply out and equate like powers of x,

    \begin{align*}  &&(x^2+1)^2 + (Bx+C)(x)(x^2+1) + (Dx+E)x &= x^4 + 1 \\ \implies && x^4 + 2x^2 + 1 + Bx^4 + Cx^3 + Bx^2 + Cx + Dx^2 + Ex &= x^4 + 1 \\ \implies && (1+B)x^4 + Cx^3 + (2 + B + D)x^2 + (C + E)x &= x^4. \end{align*}

Therefore, equating like powers of x, we have the following equations

    \begin{align*}  1+B &= 1 \\  C &= 0 \\  2+B+D &= 0 \\  C+E &= 0 \end{align*}

Solving this system we obtain

    \[ B = 0, \quad C = 0, \quad D = -2, \quad E = 0. \]

Therefore, evaluating the integral we have

    \begin{align*}  \int \frac{x^4+1}{x(x^2+1)^2} \, dx &= \int \left( \frac{A}{x} + \frac{Bx+C}{x^2+1} + \frac{Dx+E}{(x^2+1)^2} \right) \, dx \\[9pt]  &= \int \frac{1}{x} \, dx - \int \frac{2x}{(x^2+1)^2} \, dx \\[9pt]  &= \log |x| + \frac{1}{x^2+1} + C. \end{align*}